Enhancing Arabic Language Proficiency Among Islamic University Students in Indonesia Through Artificial Intelligence in the Digital Age - Agus Supriatna; Apri Wardan Ritonga; Mohammad Jailani Muhammad Musni (Tadris Al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2025)
This study aims to explore the role of Artificial Intelligence (AI) in enhancing Arabic language proficiency among students of Islamic universities in Indonesia within the context of rapid digital transformation. The research highlights the urgency of adopting modern educational tools to improve Arabic learning outcomes, especially in higher education environments where Arabic serves as the primary language for Islamic sciences. Employing a descriptive-analytical method through an extensive literature review, the study examines key AI applications in Arabic language learning, such as chatbots, machine translation, speech recognition, and adaptive assessment platforms. The findings indicate that AI can increase student engagement, provide personalized linguistic support tailored to individual needs, and foster intrinsic motivation. Moreover, AI technologies facilitate the acquisition of essential language skills—listening, reading, grammar, and writing—within a dynamic academic environment. However, challenges remain regarding digital infrastructure and limited specialized training for faculty members. The study recommends systematic and sustainable integration of AI into Arabic language programs at Islamic universities, accompanied by teacher training workshops and policy updates aligned with digital era demands.